Feminism and intersectionality - Zavos, Alexandra (The Greek Review of Social Research, 2021)
This article examines the feminist concept of intersectionality and identifies some issues that arise in relation to its genealogy, use and dissemination in gender studies and in related fields. Following a brief review of the problematic, I discuss different conceptualizations of intersectionality, as well as critiques that accompany them. In order to highlight the plasticity of the term and the dynamics of the corresponding methodology, I focus on black feminist theory, sociological approaches to social stratification and inequality, and postcolonial critiques of multiculturalism; three areas that constitute different, yet intertwined, scientific and political projects.